Active faults in Sakhalin and North of the Sea of Okhotsk: Does the Okhotsk plate really exist?. (1st June 2022) - Kozhurin, Andrey
Highlights: Active faulting around the Sea of Okhotsk, NE Asia, contradicts the model of the Okhotsk Plate. There is the Okhotsk stream moving SW relative to continental NE Asia. Kinematics of major faults in continental NE Asia is caused by their rotation by the Okhotsk stream. Abstract: Satellite images of the entire Sea of Okhotsk region were interpreted in order to reconstruct the distribution and kinematics of active faults. The interpretation argues that the Okhotsk plate in north-eastern Asia does not exist, since a fragment of its supposed northern boundary is missing (the principle of the closed plate boundary is violated). Without the Okhotsk plate, the distribution and kinematics of active faults in the Sea of Okhotsk region can be described by the motion of the Circum-Pacific Belt masses to the south-west, relative to Eurasia, and the effect of such movement on the continental boundary of the belt.